Characteristics of ABR explicit rate control algorithms in WAN environment - Kawahara, R.; Koike, A.; Ishizuka, M.; Koshiishi, M.; Kawarasaki, M. (1997 IEEE International Conference on Communications, 1997)
This paper investigates the characteristics of ABR explicit rate control algorithms in the WAN environment. We also propose two new control algorithms based only on traffic measurement. An ABR service is expected to make it possible to utilize bandwidth effectively by closed-loop congestion control, and several control algorithms have been proposed. However, for WAN environment, a long propagation control delay will affect the effectiveness of control algorithms. Additionally, if a network supports large numbers of connections, some of the algorithms may not work well. Thus, we first categorize the aim and mechanism of control algorithms, including our proposed algorithms. Then, we evaluate their characteristics by simulation in WAN environment from the viewpoint of throughput, robustness, quickness, stability, and fairness. Using this analysis, we discuss their effectiveness in WAN environment.